If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6a + -14 = 9a + -5 Reorder the terms: -14 + 6a = 9a + -5 Reorder the terms: -14 + 6a = -5 + 9a Solving -14 + 6a = -5 + 9a Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-9a' to each side of the equation. -14 + 6a + -9a = -5 + 9a + -9a Combine like terms: 6a + -9a = -3a -14 + -3a = -5 + 9a + -9a Combine like terms: 9a + -9a = 0 -14 + -3a = -5 + 0 -14 + -3a = -5 Add '14' to each side of the equation. -14 + 14 + -3a = -5 + 14 Combine like terms: -14 + 14 = 0 0 + -3a = -5 + 14 -3a = -5 + 14 Combine like terms: -5 + 14 = 9 -3a = 9 Divide each side by '-3'. a = -3 Simplifying a = -3
| 7t-15=4t-6 | | 1.25x=35.00+.75x | | r^3+6r^2-4r-24=0 | | x^2-5x-66= | | 0.2x=0.5+3 | | b^2-6b-16=0 | | -4+4k=2(3k+1) | | -5(2b+1)+(11b-3)=0 | | -0.05x-0.04=-0.01x | | 90-4y=50-2x | | -4+4k=(3k+1) | | 4(x+3)=52 | | x^2+18-16=0 | | 2x-8=12+x | | z^3-64z=0 | | .43w-11=-.57w | | 7x+2=3x+94 | | 9t^2+24tr+16r^2=0 | | 5[6-5x]=15x-35 | | 9(t-4)+5t=7(2t+5)-11 | | 8y=-4x-12 | | -28+15-22z=3 | | 3y+x=-1 | | 5(x-3)+12=-2(x-2) | | 28b^2-13b-6=0 | | t-36=-15 | | -r-10r(4p+2p)=0 | | 5x+7=4(x+13) | | t-36=-21 | | 64x^2+48xy+9y^2=0 | | 5t^3+12t^2+14t=0 | | 8y-6=14y+18 |